VLOG PROJECT IN ENHANCING STUDENTS’ SPEAKING ACHIEVEMENT - Kurnia Febianti; Sri Wahyuni; Imadona Imadona (Esteem Journal of English Education Study Programme, 2023)
The advancement of technology has provided students with numerous opportunities to explore various media that can assist them in acquiring English as a target language. This study aims to examine the progress of students' speaking skills after being taught using Vlog as a teaching medium at SMK Muhammadiyah Pagaralam. The participants in this study were tenth-grade students from SMK Muhammadiyah Pagaralam. A quasi-experimental design was employed for this research. The instruments utilized in this study included an oral test administered before and after the treatment. The data analysis results demonstrated that the students exhibited improved speaking skills after being taught using vlogs as a teaching medium. In conclusion, vlogs proved to be an effective medium for enhancing students' speaking achievements at SMK Muhammadiyah Pagaralam.